Assessing Changes in Symptoms of Depression and Anxiety During Four Weeks of Cannabis Abstinence Among Adolescents - Cooke, Megan E.; Gilman, Jodi M.; Lamberth, Erin; Rychik, Natali; Tervo-Clemmens, Brenden; Evins, A. Eden; Schuster, Randi M. (Frontiers in Psychiatry, 2021)
Background: Cannabis use is prevalent among adolescents, and many report using in attempts to alleviate negative mood and anxiety. Abstinence from substances such as alcohol and tobacco has been reported to improve symptoms of anxiety and depression. Few studies have examined the effect of cannabis abstinence on symptoms of anxiety and depression. Objective: To test the effect of four weeks of continuous cannabis abstinence on depressive and anxious symptoms. Methods: Healthy, non-treatment seeking adolescents who used cannabis at least weekly (n = 183) were randomized to either four weeks of cannabis abstinence achieved through a contingency management paradigm (CB-Abst) or cannabis use monitoring without an abstinence requirement (CB-Mon). Abstinence was assessed by self-report verified with quantitative assay of urine for cannabinoids. Anxiety and depressive symptoms were assessed weekly with the Mood and Anxiety Symptom Questionnaire (MASQ). Results: Symptoms of depression and anxiety decreased throughout the study for all participants (MASQ-AA: stnd beta = -0.08, p = 0.01, MASQ-GDA: stnd beta = -0.11, p = 0.003, MASQ-GDD: stnd beta = -0.08, p = 0.02) and did not differ significantly between randomization groups (p’s > 0.46). Exploratory analyses revealed a trend that abstinence may be associated with greater improvement in symptoms of anxiety and depression among those using cannabis to cope with negative affect and those with potentially hazardous levels of cannabis use. Conclusions: Among adolescents who use cannabis at least weekly, four weeks of cannabis abstinence was not associated with a significant change in anxiety or depressive symptoms compared to continued uses. For recreational cannabis users who may be concerned about reducing their use for fear of increased symptoms of anxiety and depression, findings suggest that significant symptom worsening may not occur within the first four weeks of abstinence. Further studies are needed in clinical populations where anxiety and depression symptoms are measured more frequently and for a longer period of abstinence. Future studies are also needed to determine whether there are subgroups of adolescents who are uniquely impacted by sustained cannabis abstinence.